Hubungan Budaya Nelayan terhadap Perekonomian dan Ekosistem Laut di Pantai Labu Kecamatan Paluh Sibaji - Raspiyahni, Raspiyahni; Lubis, Ade Irma Seftyani; Araafi, Alif; Muharani, Anisa; Ariyansyah, Fauzy; Oktapiani, Friska Dela; Ardila, Maisyah; Andaresta, Novi; Pasaribu, Syahril Budiman; Nasution, Ummi Kalsum; Ayu, Delfriana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Indonesia is known for its diverse culture and also has a large expanse of water territory. Most of Indonesia's territory consists of oceans and has great marine potential. This potential should be able to improve the welfare of the community, especially the fishermen who rely on this marine potential. However, the reality is that fishermen's lives are often plagued by poverty. Fishermen, especially laborers and traditional fishermen, are among the poorest groups in coastal areas. This research uses a qualitative descriptive research design. The research population is all fishermen in the coastal area of Pantai Labu, Palu Sibaji District. The research sample was taken using accidental sampling. Data was collected through interviews using prepared questionnaires. The research respondents totaled 30 people who work as fishermen. The findings of this research show that most fishermen still use traditional fishing gear and also make efforts to preserve the marine ecosystem, such as building fish houses and strongly prohibiting sea bombing.